(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article examines the pragmatic and ambiguous features of prepositions in English and Uzbek. Introductions are often used to set the tone, establish relationships between speakers, and provide context for a conversation. Using a combination of qualitative and quantitative analysis, this study explores how introductory words are used in both languages and the different meanings they can convey. The findings show that introductory words play a crucial role in communication and can have different interpretations depending on the context in which they are used.